Lumpy skin disease in a cow - Tse, Anne Ching-Nga; Yuen, Carlton Pak-Man (Brazilian Journal of Veterinary Pathology, 2022)
Five-year-old, spayed, stray brown cow with generalized cutaneous nodules present for a week.